Cleaning behaviour of the cichlid Mesonauta festivus in the Pantanal wetlands: evidence of a potential freshwater cleaning station. Issue 1 (2nd January 2016) - Severo-Neto, Francisco; Froehlich, Otávio
Abstract: Cleaning interactions are known among several groups of fishes, with a higher number of records for marine fish species. These temporary associations occur between one species that acts as the cleaner and the other species as the client. The interaction usually takes place within the boundaries defined by the cleaner. This site, known as the cleaning station, allows the client fish to strike a typical pose allowing the cleaner to approach, such as wide-open fins and inclined, motionless body. Few studies have reported on the cleaning behaviour of freshwater fish species, and none has reported on behaviour that could be interpreted as establishing a cleaning station. Herein we present a new record of the cleaning interaction in the Neotropics, between the cichlid Mesonauta festivus as the cleaner and three species of anostomid ( Leporinus macrocephalus, Leporinus friderici and Schizodon borellii ) as clients on Pantanal wetlands, as well as the establishment of a defined cleaning station.